Association of Tricuspid Annular Plane Systolic Excursion with Survival Time in Boxer Dogs with Ventricular Arrhythmias. (March 2015) - Kaye, B.M.; Borgeat, K.; Mõtsküla, P.F.; Luis Fuentes, V.; Connolly, D.J.
Abstract : Background: Tricuspid annular plane systolic excursion (TAPSE) is a useful estimate of right ventricular function in humans. Reference intervals for dogs have been generated, but the value of measuring TAPSE in other diseases, or investigating the association between TAPSE and outcome, is unknown. Hypothesis: TAPSE is lower in Boxer dogs with ≥50 VPCs/24 h on Holter than in dogs with fewer ventricular ectopics, and lower TAPSE is associated with a shorter survival time. Animals: Fifty Boxer dogs that presented for investigation of syncope or suspected arrhythmogenic right ventricular cardiomyopathy (ARVC) at a veterinary teaching hospital (2004–2011). Methods: Retrospective study. Clinical records, Holter, and echocardiographic data were reviewed. TAPSE was measured in a blinded manner on stored echocardiographic cine‐loops using anatomic M‐mode. Outcome information was obtained and death was classified as cardiac or noncardiac. Survival analysis was performed using Kaplan‐Meier curves and Cox proportional hazards models. Results: TAPSE was lower in Boxers with ≥50 VPCs/24 h (13.9 ± 4.04 mm) than Boxers with <50 VPCs/24 h (16.8 ± 3.21 mm; P < .001). TAPSE <15.1 mm was associated with shorter cardiac survival time in all dogs ( P = .004) and also in dogs without left ventricular dysfunction ( P = .035). When controlling for other variables, including ventricular tachycardia on Holter and left ventricular systolic dysfunction, multivariable analysis showed that TAPSE remained an independent predictor of time to cardiac death (HR >4.09, 95%CI 1.15–16.9, P < .029). Conclusions and Clinical Importance: TAPSE offers prognostic value for Boxer dogs, including those with apparently normal systolic function and ≥50 VPCs/24 h on Holter analysis.